New therapeutics for soft tissue sarcomas: Overview of current immunotherapy and future directions of soft tissue sarcomas - Seong, Gyuhee; D’Angelo, Sandra P. (Frontiers in Oncology, 2023)
Soft tissue sarcoma is a rare and aggressive disease with a 40 to 50% metastasis rate. The limited efficacy of traditional approaches with surgery, radiation, and chemotherapy has prompted research in novel immunotherapy for soft tissue sarcoma. Immune checkpoint inhibitors such as anti-CTLA-4 and PD-1 therapies in STS have demonstrated histologic-specific responses. Some combinations of immunotherapy with chemotherapy, TKI, and radiation were effective. STS is considered a ‘cold’, non-inflamed tumor. Adoptive cell therapies are actively investigated in STS to enhance immune response. Genetically modified T-cell receptor therapy targeting cancer testis antigens such as NY-ESO-1 and MAGE-A4 demonstrated durable responses, especially in synovial sarcoma. Two early HER2-CAR T-cell trials have achieved stable disease in some patients. In the future, CAR-T cell therapies will find more specific targets in STS with a reliable response. Early recognition of T-cell induced cytokine release syndrome is crucial, which can be alleviated by immunosuppression such as steroids. Further understanding of the immune subtypes and biomarkers will promote the advancement of soft tissue sarcoma treatment.